Rogalsky Effect pada Bursa Efek Indonesia Tahun 2013–2017 (Studi Kasus Indeks Saham Bisnis-27) - Muhammad Yusril Laksana Amrullah; Khairunnisa Khairunnisa (JMK (Jurnal Manajemen dan Kewirausahaan), 2019)
Market anomalies described the price of shares outstanding in the market show that performance in contravention of the concept of the capital market efficient in other words the stock price does not reflect all the information is in the capital market efficient. The purpose of this research is to see if is going on the phenomenon of market anomalies seasonal in nature namely rogalsky effect in the index bisnis-27 indonesia stock exchange a period of 2013 - 2017. A method of testing using Kolmogrov-Smirnov test to see normally distributed data, Independent Sample T-Test to hypothesis. The research data the stock price is secondary. Testing of statictic using SPSS 25 version software. The result of this research suggests that not happened Rogalsly Effect on stock index bisnis-27 period 2013 - 2017. The implications of this research indicates that appear new phenomenon but rogalsky effect that occurs on Wednesday.The results that not found Rogalsky Effect, investors can buy stock prices than on Wednesday for a cheap price and sell back in the Wednesday with higher prices especially for January to get maximum return.